Currículos de matemática do ensino médio: a polarização entre aplicações práticas e especulações teóricas - Almeida, Arlete Aparecida Oliveira de (2011)
This assignment broaches curriculum of Mathematic in high school, intending to analyze the occurrence of Mathematic when it emphasizes the practical application, focused on its theory production. Considering that in the recently discussions about this subject, there is a tendency in the official orientation, educational material and possibly in the class practice, to give priority to a mathematic with emphasis on practical application. This assignment s goal is to collect arguments that support the proposals that defend Mathematic in its purest and speculative way or in its application as an essential criterion to be taught. With this concerning, we have analyzed documents of the official, national and state curriculum, course books, and produced material considering the project Construction of the Learning and the curriculum innovation implement in Mathematic in the High School level , in what our research takes part. We have chosen two representative texts of this polarization: the Lawrence Shirley s, that emphasizes the utilitarian characteristic of the contemporary Mathematic, contributing to a more broad view of its application and the Godfrey Harold Hardy s, requiring a different view, where he says that the pure Mathematic is, in general, much more useful than the practical one, emphasizing that the most useful is the technique of the Mathematic. We have added Ole Skovsmose to the debate, for his contributions in the Mathematic critical area, essential part to complement the reflections around the Mathematic to be taught to the students. Faced with the results analysis, we have concluded that the Mathematic curriculum to the high school level needs to have a clear direction, because each choice will be reflected in the future, socially and on the individual that will be formed. The clarity of the high school courses will certainly provide the production possibilities of the curriculum to the high school level